Hydronephrosis and crossing vessels in children: Optimization of diagnostic-therapeutic pathway and analysis of color Doppler ultrasound and magnetic resonance urography diagnostic accuracy. Issue 1 (February 2018) - Wong, M.C.Y.; Piaggio, G.; Damasio, M.B.; Molinelli, C.; Ferretti, S.M.; Pistorio, A.; Ghiggeri, G.; Degl'Innocenti, M.L.; Canepa, A.; Incarbone, V.; Mattioli, G.
Summary: Introduction: Ureteropelvic junction obstruction (UPJO) is one of the most frequent urological diseases affecting the pediatric population. It can be due to both intrinsic stenosis of the junction and extrinsic causes such as the presence of crossing vessels (CVs), which can be detected by color Doppler ultrasound (CD-US). Magnetic resonance urography (MRU) is a good alternative, but sedation and infusion of a contrast agent are required. Objective: The aim of this study was to analyze the diagnostic accuracy of CD-US and MRU in visualizing CVs in pediatric hydronephrosis, in order to decide the correct diagnostic pathway in the pre-operative phase. Material and methods: A retrospective review was performed of medical records for all patients who underwent surgical treatment for hydronephrosis from August 2006 to February 2016. Ultrasound and scintigraphy had been performed on all patients. Data about CD-US and MRU were collected. A high-level technology ultrasound scanner and a 1.5 T MR scanner were used. The presence of CVs at surgery was considered the gold standard. Sensitivity, specificity, positive and negative predictive values (NPV) were calculated and reported for both of the imaging techniques. Results: A total of 220 clinical charts were reviewed. Seventy-three CVs were identified at surgery (33.2% of UPJO). The median age was statistically higher in the group with CVs compared to the group without CVs ( P < 0.001). The sensitivity and NPV of CD-US in detecting CVs were higher than MRU (sensitivity 93.3% vs. 71.7%, NPV 95.7% vs. 77.6%, respectively). Discussion: According to the data, CD-US had higher sensitivity and NPV than MRU, resulting in superior detection of CVs. It is important for a surgeon to know that a child has a CV, especially in older children in which the incidence of extrinsic UPJO is higher. The main limitation of this study was the presence of incomplete data, due to the retrospectivity. Conclusions: In the pre-operative phase, the CD-US should be considered as the investigation of choice to detect CVs in children with hydronephrosis (Summary Fig ). Moreover, CD-US has lower costs than MRU, and sedation with infusion of contrast agent is unnecessary. For the future, it could be useful to lead a prospective comparison between the two imaging techniques. Summary Fig Crossing vessel detection over the UPJ with color Doppler ultrasound.